Geological, geochemical and cosmogenic nuclides constraints from the NEEM core basal sediments, Greenland - Protin, Marie; Blard, Pierre-Henri; Tison, Jean-Louis; Dahl-Jensen, Dorthe; Steffensen, Jørgen Peder; Debaille, Vinciane; Fripiat, François; Verstraeten, David; Caffee, M; Bierman, P.R.; Corbett, L.B.; Christ, A.J. (2020)
info:eu-repo/semantics/nonPublished